Experimental analysis and modeling of micro-texture and vickers hardness impact on polished stone value in high-friction aggregates - He, Zhenqing; Li, Jun; Nian, Juanni; Guan, Bowen (Frontiers in Materials, 2024)
This article intends to study the influence of micro-texture and Vickers hardness on Polished Stone Value (PSV) of four types of high friction aggregates (90# Bauxite, 75# Bauxite, Basalt and Granite) during long-term polishing process. For this purpose, profile roughness, Vickers hardness and PSV were tested. The relationship between profile roughness, Vickers hardness and PSV were analyzed with gray correlation analysis and mathematical fitting. The results show that arithmetic mean roughness (Ra) and maximum height (Rz) influenced PSV significantly while root mean square height (Rq), skewness (Rsk) , kurtosis (Rku) and load length ratio (Rmr (c)) had a relatively weak effect.Because of the high correlation with PSV, Ra and Rz were chosen as indicators, and the relationship between variables (Ra, Rz) and PSV was established. There is a good liner relationship between the attenuation rate of Ra and Rz per polishing cycle (K1 and K2) and Vickers hardness. Finally, a model of estimation of polished stone value of high friction aggregate based on micro-texture and Vickers hardness during long-term polishing process is developed. Measuring the profile roughness and Vickers hardness to obtain Ra, Rz, H correlation values and substituting them into the modelling equations in this paper can be used for optimal selection and life estimation of high friction aggregates, which belong to the raw materials, and the optimal selection of high friction aggregates will be helpful for the design of wear-resistant coatings, especially for high friction surface treatments.